Light alters the impacts of nitrogen and foliar pathogens on the performance of early successional tree seedlings - Brown,Alexander; Heckman,Robert W. (PeerJ, 2021)
Light limitation is a major driver of succession and an important determinant of the performance of shade-intolerant tree seedlings. Shade intolerance may result from a resource allocation strategy characterized by rapid growth and high metabolic costs, which may make shade-intolerant species particularly sensitive to nutrient limitation and pathogen pressure. In this study, we evaluated the degree to which nitrogen availability and fungal pathogen pressure interact to influence plant performance across different light environments. To test this, we manipulated nitrogen availability (high, low) and access by foliar fungal pathogens (sprayed with fungicide, unsprayed) to seedlings of the shade-intolerant tree, Liquidambar styraciflua, growing at low and high light availability, from forest understory to adjacent old field. Foliar fungal damage varied with light and nitrogen availability; in low light, increasing nitrogen availability tripled foliar damage, suggesting that increased nutrient availability in low light makes plants more susceptible to disease. Despite higher foliar damage under low light, spraying fungicide to exclude pathogens promoted 14% greater plant height only under high light conditions. Thus, although nitrogen availability and pathogen pressure each influenced aspects of plant performance, these effects were context dependent and overwhelmed by light limitation. This suggests that failure of shade-intolerant species to invade closed-canopy forest can be explained by light limitation alone.
Keywords: American sweetgum; Foliar fungal pathogens; Old field succession; Pseudocercospora liquidambaricola; Shade tolerance; Top-down; Bottom-up